Potency of Anticandida extract combine by in vitro and in vivo - Ning Rintiswati, Ning Rintiswati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Background: Antifungal agents are routinely used for the treatment of fungal infections. It is very likely however, that resistance of fungi to antifungal agents will emerge in the near future and the development new antifungal agent is very slow. To cope with the problem, it is important to search new antifungal agent from natural resources for yhe treatment of various diseases. It was also reported that bee honey has antibacterial property.Objective: To know the in vitro and in vivo effect of crude honey, aether-extracted honey and its residual part on Candida albicansMethods: Samples used in this experiment were crude honey, aether-extracted honey and residual part of extracted honey. Each sample was tested for its anticandidal activity with macrobroth dilution method using casein-yeast extract-glucose medium. Minimal inhibitory concentration and minimal fungicidal concentration were determined for each sample.Result: The result showed that extracted honey anticandidal effect in vitro at minimal inhibitory concentration was 0.3125% v/v and its residual was 25%, whereas crude honey has no inhibitory in vitro effect on Candida albicans. Minimal fungicidal concentration of extracted honey and its residual were 0.31255 and 50% v/v respectively. In vivo study showed that treatment group recovered faster than control group.Conclusion: Aether extracted honey and its residual have anticandidal activity in vitro. The extract have effect on recovery of candidal infected mice.Key words: Candida albicans - bee honey - antifungal-minimal inhibitory concentration - candidal infection recoveryÂ